DESIGN DRAWING - Ching,Francis D.K , 1943; Juroszek,Steven P (John Willey & Son Inc., 2018)
"Sales Handles-In Frank'S distinctive graphic style,over 1500 habd drawings reinforce the concepts and lessons of each chapter-expand to include new exercisw and examples that range in complexity.